Appearance mechanism and prevention technology of impact energy of roadway floor on additional load - Hui Wei; Xiaoxing Li; Dezhi Shi; Dongdong Qin; Kai Wang (Scientific Reports)
Abstract With the increasing strength and depth of coal mining, the proportion of mining under complex conditions is becoming more and more significant. The energy accumulation model and mechanical model of suspended roof are established by analyzing of the stress distribution law of suspended roof, which is based on complicated geological conditions of hard roof, hard coal and soft floor. The study of energy evolution processes of the soft floor and suspended roof suggest that the energy releasing caused by soft floor failure is the fundamental reason for rock burst, and the suspended roof also has an influence on the floor damage. Prevention technology of side-bottom pressure relief and roof cutting by large diameter drilling hole on coal and surrounding factors are proposed by this study. After applying the above method to the 1306 working face, the coal dusts in the three boreholes of the coal wall are reduced from 2.9 kg/m, 3.1 kg/m, 3.0 kg/m to 2.5 kg/m, 2.6 kg/m, 2.7 kg/m respectively, and the average amount of coal dusts is reduced from 3.0 to 2.6 kg/m, which is far less than the critical value. Therefore, this study has achieved effective prevention and control of rockburst in roadway under the complex conditions of hard suspended roof, impact coal mass, and soft floor, ensuring safe mining of the working face and providing methodological reference for similar mining conditions.